STRATEGI OPTIMALISASI PENERIMAAN RETRIBUSI PASAR DI KABUPATEN ROKAN HILIR - Leo Alhaksbi; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The research present describe the optimalization of market retribution. From the market retribution data, in 2009 realization of market retribution has a target, but in 2010 until 2013 the market retribution was never get a target realization by Clean, Park and Market Agency Rokan Hilir Agency. The decrease of market retribution cause of some factor by minimalization of market retribution, minimalization of human resources in market retribution and the other factors.The research use the methode are qualitative methodes that analyze problem research by describe the subject and object conditions based on real fact. This research use location in Rokan Hilir Regency and researcher collect data from books, government regulation, jurnal, mass media, website and deep interview with informan likes Head of Clean, Park and Market Agency Rokan Hilir Agency, Head of section Clean, Park and Market Agency Rokan Hilir Agency, staff of market retribution and retributors.The conclution of this research are strategy of Clean, Park and Market Agency Rokan Hilir Agency to optimlaization of market retribution are values strategy, planning strategy, position strategy, vision mission strategy and tactics step strategy. The factors that influence of strategy of Clean, Park and Market Agency Rokan Hilir Agency to optimlaization of market retribution are minims of coordination with the other agency, minimize of socialization of regulation, minimize of controlling agency, staff positioning of agency and minimize of insentive for staff retributors.Keywords: market retributions, optimalization strategy and influence factors.